Expression pattern of immediate early genes in the cerebellum of D1R KO, D2R KO, and wild type mice under vestibular-controlled activity - Nakamura, Toru; Sato, Asako; Kitsukawa, Takashi; Sasaoka, Toshikuni; Yamamori, Tetsuo (Frontiers in Cell and Developmental Biology, 2015)
We previously reported the different motor abilities of D1R knockout (KO), D2R KO and wild-type (WT) mice. To understand the interaction between the cerebellum and the striatal direct and indirect pathways, we examined the expression patterns of immediate early genes (IEG) in the cerebellum of these three genotypes of mice. In the WT naive mice, there was little IEG expression. However, we observed a robust expression of c-fos mRNA in the vermis and hemisphere after running rota-rod tasks. In the vermis, c-fos was expressed throughout the lobules except lobule 7, and also in crus 1 of the ansiform lobule (Crus1), copula of the pyramis (Cop) and most significantly in the flocculus in the hemisphere. jun-B was much less expressed but more preferentially expressed in Purkinje cells. In addition, we observed significant levels of c-fos and jun-B expressions after handling mice, and after the stationary rota-rod task in naive mice. Surprisingly, we observed significant expression of c-fos and jun-B even 30 min after single weighing. Nonetheless, certain additional c-fos and jun-B expressions were observed in three genotypes of the mice that experienced several sessions of motor tasks 24 h after stationary rota-rod task and on days 1 and 5 after rota-rod tasks, but no significant differences in expressions after the running rota-rod tasks were observed among the three genotypes. In addition, there may be some differences 24 h after the stationary rota-rod task between the naive mice and the mice that experienced several sessions of motor tasks.